Conceptual Design On N16 Decay Chamber For Modified TRIGA-2000 With Plate-Type Fuel - Sukmanto Dibyo; Surian Pinem; V.I.S Wardhani (Pusat Kajian Sistem Energi Nuklir, Badan Tenaga Nuklir Nasional, 2018)
Conceptual Design On N16 Decay Chamber For Modified TRIGA-2000 With Plate-Type Fuel. the TRIGA-2000 is a research reactor in bandung that will be modified using plate-type fuel. The reactor core cooling system is changed from the natural convection cooling mode to the forced convection mode. The purpose of the study is to assess the conceptual design for the decay chamber of N16 nuclide in the primary cooling system of the reactor. In this design, the hold-up system decays the nuclide of N16 resulted from neutron activation product. In the period of 50 seconds, the activity of N16 (T1/2= 7.13 seconds) decays 7 time from half life to low level. The cube shape of decay chamber is provided a plate with 4 hollows and facility to flush the cavitation bubbles. The decay chamber, which is submerged into the bulk shielding as located outside of the reactor pool. The conceptual design uses the Fluent software compared with the analytical estimation for flow velocity in the decay chamber. The result shows a good agreement range with the analytical estimations. The uniform flow profile can be obtained at the velocity of about 0.4 m/s. Water flow life time of 50 seconds in the decay chamber with the capacity of 3.5 m3 is able to decay the N16 nuclide to low level. This decay chamber is expected to contribute in completing the design of reactor primary coolant system using the forced convection mode.